Nutrient-Poor Breeding Substrates of Ambrosia Beetles Are Enriched With Biologically Important Elements - Lehenberger, Maximilian; Foh, Nina; Göttlein, Axel; Six, Diana; Biedermann, Peter H. W. (Frontiers in Microbiology, 2021)
Fungus-farming within galleries in the xylem of trees has evolved independently in at least twelve lineages of weevils (Curculionidae: Scolytinae, Platypodinae) and one lineage of ship-timber beetles (Lymexylidae). Jointly these are termed ambrosia beetles because they actively cultivate nutritional “ambrosia fungi” as their main source of food. The beetles are obligately dependent on their ambrosia fungi as they provide them a broad range of essential nutrients ensuring their survival in an extremely nutrient-poor environment. While xylem is rich in carbon (C) and hydrogen (H), various elements essential for fungal and beetle growth, such as nitrogen (N), phosphorus (P), sulfur (S), potassium (K), calcium (Ca), magnesium (Mg), and manganese (Mn) are extremely low in concentration. Currently it remains untested how both ambrosia beetles and their fungi meet their nutritional requirements in this habitat. Here, we aimed to determine for the first time if galleries of ambrosia beetles are generally enriched with elements that are rare in uncolonized xylem tissue and whether these nutrients are translocated to the galleries from the xylem by the fungal associates. To do so, we examined natural galleries of three ambrosia beetle species from three independently evolved farming lineages, Xyleborinus saxesenii (Scolytinae: Xyleborini), Trypodendron lineatum (Scolytinae: Xyloterini) and Elateroides dermestoides (Lymexylidae), that cultivate unrelated ambrosia fungi in the ascomycete orders Ophiostomatales, Microascales, and Saccharomycetales, respectively. Several elements, in particular Ca, N, P, K, Mg, Mn, and S, were present in high concentrations within the beetles’ galleries but available in only very low concentrations in the surrounding xylem. The concentration of elements was generally highest with X. saxesenii, followed by T. lineatum and E. dermestoides, which positively correlates with the degree of sociality and productivity of brood per gallery. We propose that the ambrosia fungal mutualists are translocating essential elements through their hyphae from the xylem to fruiting structures they form on gallery walls. Moreover, the extremely strong enrichment observed suggests recycling of these elements from the feces of the insects, where bacteria and yeasts might play a role.